Valproic Acid Synergizes With Cisplatin and Cetuximab in vitro and in vivo in Head and Neck Cancer by Targeting the Mechanisms of Resistance - Iannelli, Federica; Zotti, Andrea Ilaria; Roca, Maria Serena; Grumetti, Laura; Lombardi, Rita; Moccia, Tania; Vitagliano, Carlo; Milone, Maria Rita; Ciardiello, Chiara; Bruzzese, Francesca; Leone, Alessandra; Cavalcanti, Ernesta; et al. (Frontiers in Cell and Developmental Biology, 2020)
Recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC) is a devastating malignancy with a poor prognosis. The combination of cisplatin (CDDP) plus cetuximab (CX) is one of the standard first-line treatments in this disease. However, this therapeutic regimen is often associated with high toxicity and resistance, suggesting that new combinatorial strategies are needed to improve its therapeutic index. In our study, we evaluated the antitumor effects of valproic acid (VPA), a well-known antiepileptic agent with histone deacetylase inhibitory activity, in combination with CDDP/CX doublet in HNSCC models. We demonstrated, in HNSCC cell lines, but not in normal human fibroblasts, that simultaneous exposure to equitoxic doses of VPA plus CDDP/CX resulted in a clear synergistic antiproliferative and pro-apoptotic effects. The synergistic antitumor effect was confirmed in four different 3D-self-assembled spheroid models, suggesting the ability of the combined approach to affect also the cancer stem cells (CSCs) compartment. Mechanistically, VPA enhanced DNA damage in combination treatment by reducing the mRNA expression of ERCC1, a critical player in DNA repair, and by increasing CDDP intracellular concentration via up-regulation at transcriptional level of CDDP influx channel copper transporter 1 (CTR1) and down-regulation of the ATPAse ATP7B involved in CDDP-export. VPA also induced a dose-dependent down-regulation of epidermal growth factor receptor (EGFR) expression and of MAPK and AKT downstream signaling pathways and prevent CDDP and/or CX induced EGFR nuclear translocation, a well-known mechanism of resistance to chemotherapy. Indeed, VPA impaired the transcription of genes induced by non-canonical activity of nuclear EGFR, such as cyclin D1 and thymidylate synthase. Finally, we confirmed the synergistic antitumor effect also in vivo in both heterotopic and orthotopic models, demonstrating that the combined treatment completely blocked HNSCC xenograft tumors growth in nude mice. Overall, the introduction of a safe and generic drug such as VPA into the conventional treatment for R/M HNSCC represents an innovative and feasible antitumor strategy that warrants further clinical evaluation. A phase II clinical trial exploring the combination of VPA and CDDP/CX in R/M HNSCC patients is currently ongoing in our Institute.